Desain Kemasan Tradisional Dalam Konteks Kekinian - Benny Rahmawan Noviadji (Artika, 2014)
The diversity of traditional food is a part of the Indonesian nation's wealth . Along with the development of technology and lifestyle , traditional food packaging community naturally becoming obsolete due to packaging impressed judged to be synonymous with cheap and dirty , unhygienic and impractical . Then slowly replaced with materials such as plastic , cans and Styrofoam are prone to pollute the environment .Several types of traditional packaging using natural ingredients . But it is not designed as a serious and still serves as a container or wrapper only, not so into consideration in terms of increased sales , image enhancement , local identity , not even thought about issues such as environmentally friendly recycle , reduce, and reuse . The role of the designer is to maintain the existence of the traditional packaging that still exist and more appreciated by giving traditional packaging solutions in creating more dynamic in terms of several aspects when faced with the current conditions , among others, in terms of novelty designs that are more innovative and unique selling points high given the increasing number of products on the market . A touch of unique design will be able to make traditional packaging into an exclusive packaging . Traditional packaging was also created to be able to maintain the characteristic of local culture without ignoring local identity to represent the local culture . More important consideration also needs to pay attention to in terms of eco-friendly , considering the waste problem is now starting to bloom voiced , so it should be easy to traditional packaging for recycling . Present context is intended to things above solving traditional packaging design solutions to some of the conditions existing problems.